Phenology Dynamics: Flowering and Fruit Development of Prabu Bestari Grape Variety in Denpasar - Ni Ketut Karina Sari; Dewa Ayu Ari Ari Febriayanti; Ni Nyoman Ari Putri Murtiyah; Dicky Marsadi (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2025)
Grape (Vitis vinifera L.) var. Prabu Bestari is an important fruit commodity, but information regarding its reproductive phenology is still minimal. This qualitative descriptive study aimed to determine the time periods required for key phenological stages, namely bud burst, bloom, fruit set, and fruit ripening (harvest), which are crucial for breeding and optimizing production. The research was conducted at the Faculty of Agriculture's Experimental Garden (0–9 masl). The observations revealed a rapid reproductive growth cycle. The average time from pruning to shoot emergence (bud burst) was 7 days after pruning (dap). The phase from bud burst to flowering lasted 18–19 days. Full bloom was very brief, lasting only 1 day, and the phase from flowering to fruit set required 1–3 days. The longest period was from fruit set to harvest, lasting 48 days. Overall, the cycle from pruning to harvest for the Prabu Bestari variety required an average of 120 dap. This phenological data provides an essential basis for effective cultivation management.